Viscosity β-coefficients and Some Thermodynamic Parameters of Niacin Drug at Different Temperatures in Aqueous Medium - Narwade, M.L.; Jumle, Ravi; Usha Wasnik, (Ms). (Asian Journal of Chemistry, 2010)
Viscosity, relative viscosity, specific viscosity of β-coefficient of niacin drug in water has been determined at five different temperatures. β-coefficient values have been found to be low but positive. This shows the niacin drug can be regarded to be structure-making in character. This is due to hydrophobic hydrations of the drug molecules. The activation parameters ΔH and ΔS have been found to be very high and positive.